Characteristics of scores used for quantitative lung ultrasound in neonates: a systematic review - Victor Sartorius; Stéphanie Brunet; Daniele De Luca (European Respiratory Review)
Background Quantitative lung ultrasound is increasingly being used in neonatology. The aim of this study is to identify the lung ultrasound scores (LUS) available for use in neonates, describe their characteristics and determine which LUS are most used and validated. Methods A systematic review of the literature was conducted following PRISMA-S (Preferred Reporting Items for Systematic Reviews and Meta-analysis Protocols extension for reporting literature searches in systematic reviews) guidelines. Articles describing LUS in newborn animals and human neonates, published up to March 2024, were searched in the PubMed and Embase databases. Results Out of 757 identified studies, 121 were included. Most of the articles were published in the past 5 years, predominantly by European investigators. They described 32 different LUS. Only 10 (31.4%) of these LUS had undergone at least one validation attempt and only 15 (48.4%) used the four-step scoring scale (i.e. scored from 0 to 3) based on classical lung ultrasound patterns originally described and well established in adult critical care medicine. The most common (49 (40.5%) of all the articles) neonatal score (published by Brat et al. in 2015) was based on this classical grading system. The most commonly used score was also validated using the greatest number of techniques and applied to all major neonatal respiratory disorders. Its simplified version is used to analyse six chest areas (anterior and lateral) to guide surfactant administration, while its extended version includes 10 areas by adding four posterior ones. Conclusions The most commonly used and validated score, consistent with adult critical care practice, should be the standard for assessing lung aeration in neonates.